Harnessing Integrated Vector Management for Enhanced Disease Prevention. Issue 1 (January 2017) - Chanda, Emmanuel; Ameneshewa, Birkinesh; Bagayoko, Magaran; Govere, John M.; Macdonald, Michael B.
Abstract : The increasing global threat of emerging and re-emerging vector-borne diseases (VBDs) poses a serious health problem. The World Health Organization (WHO) recommends integrated vector management (IVM) strategy for combating VBD transmission. An IVM approach requires entomological knowledge, technical and infrastructure capacity, and systems facilitating stakeholder collaboration. In sub-Saharan Africa, successful operational IVM experience comes from relatively few countries. This article provides an update on the extent to which IVM is official national policy, the degree of IVM implementation, the level of compliance with WHO guidelines, and concordance in the understanding of IVM, and it assesses the operational impact of IVM. The future outlook encompasses rational and sustainable use of effective vector control tools and inherent improved return for investment for disease vector control. Trends: Vector-borne disease endemic countries in sub-Saharan Africa have embarked on consolidating strategic and operational frameworks for the IVM approach. Countries are still grappling with the challenges of capacity building for human resources and infrastructure that are key in operational deployment of the IVM strategy. Entomological surveillance to generate evidence required for rational decision making to, in turn, optimize utilization of resources is still limited. Intersectoral collaboration to facilitate complete harnessing of the IVM approach for exploiting its potential for integrating across diseases control remains minimal. The evidence for operational impact of the IVM strategy on risk of transmission, disease burden, cost-effectiveness, ecological soundness, organization, and management remains minimal.